Next‐generation peptide vaccines for advanced cancer. Issue 1 (4th December 2012) - Yamada, Akira; Sasada, Tetsuro; Noguchi, Masanori; Itoh, Kyogo
<x xml:space="preserve">Abstract</x> Many clinical trials of peptide vaccines have been carried out since the first clinical trial of a melanoma antigen gene‐1‐derived peptide‐based vaccine was reported in 1995. The earlier generations of peptide vaccines were composed of one to several human leukocyte antigen class I‐restricted CTL‐epitope peptides of a single human leukocyte antigen type. Currently, various types of next‐generation peptide vaccines are under development. In this review, we focus on the clinical trials of the following categories of peptide vaccines mainly published from 2008 to 2012: (i) multivalent long peptide vaccines; (ii) multi‐peptide vaccines consisting of CTL‐ and helper‐epitopes; (iii) peptide cocktail vaccines; (iv) hybrid peptide vaccines; (v) personalized peptide vaccines; and (vi) peptide‐pulsed dendritic cell vaccines. (Cancer Sci 2013; 104: 15–21)